Case report: Primary mediastinal Ewing’s sarcoma presenting with chest tightness - Cui, Manman; Zhai, Duchang; Liu, Yan; Zhou, Xiuzhi; Wang, Tingting; Wang, Lihuan; Cai, Wu; Fan, Guohua; Ju, Shenghong (Frontiers in Oncology, 2023)
Ewing’s sarcoma/primitive neuroectodermal tumour family is a part of a rare group of malignant neoplasms, whose pathological morphological features are small round cells. Extraskeletal Ewing’s sarcoma is a more uncommon primary tumour. Herein, we report the case of a 66-year-old man who complained of chest tightness. Subsequent chest CT scans revealed an irregular and uneven density mass on the right side of the anterior mediastinum with invasion of the superior vena cava, pericardium and right lung. The patient’s clinical symptoms were improved after performing excision of the mediastinal lesions under cardiopulmonary bypass. Based on histological and immunohistochemical findings, the tumour was diagnosed as extraskeletal Ewing’s sarcoma.